Reconstruction of the Mandatory Rehabilitation Policy for Drug Abusers in the Implementation of Law Number 35 of 2009 concerning Narcotics Based on Integrated Assessment to Suppress Recidivism in Drug Crimes - Dionisius Yudi Christiano; Sutrisno Sutrisno; Kif Aminanto (Indonesian Journal Publisher, 2026)
This study aims to analyze and reconstruct the mandatory rehabilitation policy for drug abusers in the Indonesian legal system to reduce recidivism of drug crimes. The study employs a normative juridical method with a statutory and conceptual approach, by examining the provisions of Law Number 35 of 2009 concerning Narcotics, specifically Articles 54, 103, and 127, and their relationship to Law Number 22 of 2022 concerning Corrections and Law Number 17 of 2023 concerning Health. The results of the study indicate inconsistencies in norms and the dominance of a criminal approach in practice, which is exacerbated by the weak implementation of integrated assessments and disharmony between the legal and health sectors, resulting in overcrowding of correctional institutions and high recidivism rates. Therefore, this study proposes a reconstruction of rehabilitation policy based on integrated assessments by strengthening the position of assessment results as a binding basis, limiting the discretion of law enforcement officers, and integrating penal and non-penal approaches into a coherent system. The reconstruction is expected to create a more effective, equitable, and recovery-oriented drug abuse management system.